On continuous variations of trajectories of differential inclusion with unbounded right-hand side. (2nd April 2020) - Polovinkin, Evgenii S.
ABSTRACT: The property of the continuous dependence of the trajectories of the differential inclusion with a measurable pseudo-Lipschitz unbounded right-hand side on the initial approximations in Euclidean space is proved. This property is an important part of the direct method of obtaining the necessary optimality conditions in the extremal problems with constraints in the form of a differential inclusion.